On the Validity of the Cosmic No-hair Conjecture in some Conformal-violating Maxwell Models - Do, Quoc Tuan (H. : ĐHQGHN, 2019)
We will present main results of our recent investigations on the validity of the cosmic no-hair conjecture proposed by Hawking and his colleagues in some conformal-violating Maxwell models, in which a scalar field or its kinetic term is non-trivially coupled to the electromagnetic field. In particular, we will show that the studied models really admit the Bianchi type I metrics, which are homogeneous but anisotropic space time, as their stable cosmological solutions. Hence, these models turn out to be counterexamples to the cosmic no-hair conjecture